Maximum principle for the Laplacian with respect to the measure in a domain of the Hilbert space - Bogdanskii, Yu. V.; Богданский, Ю. В.; Богданский, Ю. В. (Institute of Mathematics, NAS of Ukraine, 2016)
We obtain the maximum principle for two versions of the Laplacian with respect to the measure, namely, for the “classical” and “$L^2$” versions in a domain of the Hilbert space.